Pengaruh Perkembangan Infrastruktur Terhadap Pertumbuhan Ekonomi Kota Banda Aceh - Almismary, MF Dewantara; Wahyono, Hadi (Jurnal Pembangunan Wilayah dan Kota, 2020)
Economic growth can caused by various factors, one of them is capital growth. Capital in the form of availability of  good quality  infrastructure will increase investment, connectivity, economic growth and human welfare. After the Tsunami, Banda Aceh focused on re-providing infrastructure. Some of infrastructure that developed very prominent are: electricity, clean water, education and health. At the same time, the economic growth in Banda Aceh has increased, but the rate of economic growth tends to fluctuate and in 2017, the rate of economic growth is only 3.05%. This study aims to determine the effects of infrastructure development on economic growth in Banda Aceh. This study use quantitative descriptive method with multiple linear regression analysis tools. The data used came from PLN Banda Aceh, PDAM Tirta Daroy and BPS Banda Aceh (2003-2017). The variables in this study consisted of the dependent variable: economic growth, and independent variables: road infrastructure, clean water infrastructure, electricity infrastructure, education infrastructure and health infrastructure. The results show that there was an effects between infrastructure development on economic growth in Banda Aceh. Infrastructure that has a significant effects on economic growth is  clean water infrastructure, education infrastructure and health infrastructure, while road infrastructure and electricity infrastructure has no effects on economic growth. Base on the results, the government should make policies to increasing the quantity and quality of infrastructure. It will assist in promoting economic growth in the future.